Social movements in Chile : organization, trajectories, and political consequences - Donoso, Sofia ; Bülow, Marisa von (Palgrave Macmillan, 2020)
Contents: 1. Introduction: Social movements in contemporary Chile -- 2. Shifting relationships between social movements and institutional politics -- 3. "Outsider" and "insider" strategies: Chile's Student Movement, 1990-2014 -- 4. From cooperation to confrontation: The Mapuche Movement and its political impact, 1990-2014 -- 5. Democratizing the flows of democracy: Patagonia sin Represas in the awakening of Chile's civil society -- 6. Feminism and gender policies in post-dictatorship Chile (1990-2010) -- 7. Coping with neoliberalism through legal mobilization: the Chilean labor movement's new tactics and allies -- 8. Chilean social movements and party politics in comparative perspective: Conceptualizing Latin America's "third generation" of anti-neoliberal protest -- 9. Post-transition social movements in Chile in comparative perspective.